Karakteristik Fisik Tanah Menurut Tipe Penggunaan Lahan di Negeri Tawiri Sesuai Tata Ruang Kota Ambon - Parmenas G Kastanya; Conradus Ufie; Ferad Puturuhu (JURNAL BUDIDAYA PERTANIAN, 2019)
This study aims to identify land-use changes and soil physical characteristics and to determine the suitability of present land use in Tawiri to Ambon City Spatial Planning. This research was carried out in the Tawiri Village (Negeri) of Ambon City in June-July 2018 by using a survey method with transect/lane observation distance that was made to cut the types of land use in the area according to Ambon City Spatial Planning. The results of this study are 1) the types of land use found in the five transect lines at Tawiri Village research sites were: secondary dryland forests, mixed dryland agriculture, dryland agriculture, grass/shrubs, settlements, sago, and mangrove areas; 2) physical characteristics of soil and environment showed differences in land use types and soil physical properties, namely: land with altitude ± 45-335 m above sea level, hilly/mountainous land forms, hill and mountain reliefs, slopes between 20°-220° (2- 25%), had ± three layers of soil with varying depths of 0-> 40 cm; had soil characteristics of 2.5 YR (red) and 7.5 YR (red, reddish yellow, brown to strong brown); textures of clay, clay sand and sandy clay; classified as humid; pH 6-7; and had a distribution of organic materials which varied from low to high; and 3) The actual land use that was the same as that of the spatial designation in Tawiri Village was mostly almost suitable, those who were not suitable were the settlements which were around 78% in the coastal border. Keywords: characteristics, soil physics, land use ABSTRAK Penelitian ini bertujuan mengidentifikasi perubahan tipe penggunaan lahan dan kondisi karakteristik fisik tanah, dan mengetahui kesesuaian pemanfaatan lahan dengan tata ruang Kota Ambon di wilayah Negeri Tawiri. Penelitian ini dilaksanakan di Negeri Tawiri Kota Ambon pada bulan Juni-Juli 2018 dengan menggunakan metode survei dengan jarak observasi transek/jalur dibuat memotong tipe-tipe penggunan lahan dalam kawasan sesuai arahan Tata Ruang Kota Ambon. Hasil penelitian ini yaitu: 1) Tipe penggunaan lahan yang ditemukan pada lima jalur transek di lokasi penelitian Negeri Tawiri adalah: hutan lahan kering sekunder, pertanian lahan kering campuran, pertanian lahan kering, rumput/semak belukar, permukiman, sagu, dan mangrove; 2) Karakteristik fisik tanah dan lingkungan menunjukkan perbedaan pada tipe penggunaan lahan dan sifat fisik tanah yaitu: tanah dengan ketinggian tempat ± 45-335 m dpl, bentuk lahan perbukitan/pegunungan, relief bukit dan gunung, lereng antara 20°-220° (2-25%), memiliki ± 3 lapisan tanah dengan kedalaman bervariasi antara 0->40 cm; memiliki ciri tanah: warna 2,5 YR (merah) dan 7,5 YR (merah, kuning kemerahan, cokelat hingga cokelat kuat); tekstur lempung, pasir berlempung dan lempung liat berpasir; tergolong lembab; pH 6-7; dan memiliki sebaran BO yang bervariasi dari sedikit hingga banyak; dan 3) Penggunaan lahan aktual yang sama dengan peruntukan tata ruang di Negeri Tawiri hampir sebagian besar sesuai, yang tidak sesuai hanyalah permukiman yang berada sekitar 78% di sempadan pantai. Kata kunci: fisik tanah, karakteristik, penggunaan lahan